Spatial quality framework for experiential learning environment in visitor centre - Mohd Kamal, Siti Khadijah; Zainonabidin, Azman; Abdul Halim Choo, Iryani; Samsudin, Nor Syamimi (Universiti Teknologi MARA, Perak, 2025)
Tourism has increasingly focused on offering educational value through hands-on, immersive learning experiences. While a lot of research has explored the educational and economic benefits of museums and agritourism, less attention has been given to how the physical space itself affects learning and shapes visitor perceptions, particularly in agricultural visitor centres. This study explored the role of spatial design in enhancing experiential learning within agritourism visitor centres. It aims to develop a conceptual framework that integrates experiential learning theories with key spatial design elements to build more engaging and educational environments. A better understanding of how experiential learning principles can be applied in these spaces to enhance visitor experiences. To achieve this, the study adopted a qualitative approach in three stages: reviewing relevant literature to build theoretical insights, analysing case studies to understand how spatial elements are used, and developing a conceptual framework based on these findings. The study revealed that interactive exhibits, reflective spaces, multi-sensory experiences, and physical layouts that encourage movement and exploration all play vital roles in enhancing the learning experience. This research offers valuable contributions to the fields of education, architecture, and tourism by providing practical recommendations for designing agricultural visitor centres that offer meaningful educational experiences. By improving how these spaces are designed, the study shows how visitor engagement in agritourism can be significantly enhanced, making learning more impactful and enjoyable.